2006
DOI: 10.1152/jn.00757.2005
|View full text |Cite
|
Sign up to set email alerts
|

Store Calcium Mediates Cholinergic Effects on mIPSCs in the Rat Main Olfactory Bulb

Abstract: The significance of endoplasmic reticulum (ER) store calcium in modulating transmitter release is slowly gaining recognition. One transmitter system that might play an important role in store calcium modulation of transmitter release in the CNS is acetylcholine (ACh). The main olfactory bulb (OB) receives rich cholinergic innervation from the horizontal limb of the diagonal band of Broca and blocking cholinergic signaling in the bulb inhibits the ability of animals to discriminate between closely related odors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 61 publications
2
33
1
Order By: Relevance
“…Our findings in the AOB are different from previous work in the OB, where the carbachol-induced increase in spontaneous GABA currents was blocked by the intracellular calcium store blocker thapsigargin, suggesting that calcium released from internal stores stimulated GABA release (Ghatpande et al, 2006). In contrast, in the AOB, the intracellular calcium store blocker 2-APB did not inhibit the carbachol effect; instead, a different mechanism, the closure of KCNQ channels by M1 stimulation, was implicated.…”
Section: Differences Between the Aob And The Olfactory Bulb (Ob)contrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings in the AOB are different from previous work in the OB, where the carbachol-induced increase in spontaneous GABA currents was blocked by the intracellular calcium store blocker thapsigargin, suggesting that calcium released from internal stores stimulated GABA release (Ghatpande et al, 2006). In contrast, in the AOB, the intracellular calcium store blocker 2-APB did not inhibit the carbachol effect; instead, a different mechanism, the closure of KCNQ channels by M1 stimulation, was implicated.…”
Section: Differences Between the Aob And The Olfactory Bulb (Ob)contrasting
confidence: 99%
“…Confirmed actions of ACh in the AOB, however, have not been demonstrated. Though cholinergic action increases spontaneous mIPSCs in the olfactory bulb (Castillo et al, 1999;Ghatpande et al, 2006), this has not been shown in the AOB. As the effects of some cholinergic receptors are linked to the phospholipase C (PLC) pathway via the Gq11G-protein (see for review), we hypothesized that cholinergic stimulation has actions on mIPSCs similar to mGluR1 and noradrenergic !1 receptors stimulations that are also linked to Gq11G-protein.…”
Section: Introductionmentioning
confidence: 98%
“…ACh enhances GC excitability by inhibiting two potassium currents, I M and I AHP , which underlie frequency adaptation and are responsible for generating medium and slow AHP responses (respectively) in GCs. Blockage of these two currents uncovers a Ca 2ϩ -activated nonspecific cation current I CAN that transforms the AHP into a sustained ADP (Pressler et al 2007;Smith and Araneda 2010); the resulting synaptic potentiation requires calcium release from internal stores in the endoplasmic reticulum (Ghatpande et al 2006). In contrast, NE alters GC excitability nonmonotonically by modulating an ohmic potassium current, I KL (Nai et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…ACh in the OB acts on both nicotinic and muscarinic receptors (Castillo et al 1999;Ghatpande et al 2006;Pressler et al 2007), which are substantially segregated to different OB layers; nicotinic receptors are typically located within the glomerular and mitral cell (MC) layers, whereas muscarinic receptors are located in the granule cell (GC) layer and in the external plexiform layer (EPL), within which GCs and MCs interact synaptically. In vitro, the activation of nicotinic receptors has been shown to depolarize MCs (Castillo et al 1999;D'Souza and Vijayaraghavan 2012); earlier in vivo studies also suggested that activation of nicotinic receptors would increase firing in periglomerular cells (Ravel et al 1990), a finding that has been supported by recent slice data (D'Souza and Vijayaraghavan 2012).…”
mentioning
confidence: 99%
“…VGCCs play important roles in mediating transmitter release at mitral cell-to-granule cell dendrodendritic synapses and are involved in norepinephrine-and acetylcholine-induced increases in IPSCs in mitral cells (Araneda and Firestein, 2006;Ghatpande et al, 2006). To investigate whether VGCCs are involved in DHPG-induced increases in mIPSCs in mitral cells, DHPG was applied in the presence of CNQX-APV-TTX and the VGCC blockers Cd 2ϩ (100 M) and Ni 2ϩ (1 mM).…”
Section: Dhpg-evoked Increase In Mipscs Is Vgcc Dependentmentioning
confidence: 99%